International Yearbook of Soil Law and Policy 2019 - Ginzky, Harald; Dooley, Elizabeth; Heuser, Irene L.; Kasimbazi, Emmanuel (International Yearbook of Soil Law and Policy, 2021)
This book presents an important discussion on the implementation of sustainable soil management in Africa from a range of governance perspectives. It addresses aspects such as the general challenges in Africa with regard to soil management; the structural deficiencies in legal, organizational and institutional terms; and specific policies at the national level, including land cover policies and persistent organic pollutants. This fourth volume of the International Yearbook of Soil Law and Policy is divided into four parts, the first of which deals with several aspects of the theme "sustainable soil management in Africa." In turn, the second part covers recent international developments, the third part presents regional and national reports (i.a. Mexico, USA and Germany), and the fourth discusses cross-cutting issues(i.a. on rural-urban interfaces).